Performance improvement of projection-type multiview holographic three-dimensional display using spatial light modulators. (June 2020) - Su, Yanfeng; Tang, Xinyue; Cai, Zhijian; Wu, Jianhong; Chen, Yun; Hua, Minjie; Wan, Wenqiang
Highlights: An optimization method of multiview holographic 3D display is proposed. Seamless mosaic of holographic reconstructed images of multiple CGHs is achieved. Multiview 3D display with more viewpoints is experimentally realized. Multiview 3D display with higher resolution is also experimentally realized. Abstract: Projection-type multiview holographic three-dimensional (3D) display using a single spatial light modulator (SLM) and a directional diffractive device (DDD) composed of pixelated gratings is able to present 3D scenes with wide viewing angle and significantly reduced data volume. However, there are still several limitations on the display performance, such as finite number of viewpoints and low resolution for each view. In this paper, we propose an optimization method of projection-type multiview holographic 3D display by using multiple SLMs and a large-area DDD, where the total valid pixels used for multiview 3D display are substantially increased thanks to the seamless mosaic of holographic reconstructed images of multiple computer-generated holograms (CGHs) displaying on the SLMs so that the display performance can be noticeably improved. Two verification experiments are performed by combining two phase-only SLMs with an 8-view and a 4-view DDDs, respectively. The experimental results confirm that the crosstalk-free multiview holographic 3D displays with more viewpoints or higher resolution are successfully achieved, verifying the effectiveness of the proposed method.